(untitled) - Wolf, Ken (New York, 1988)
The book summarizes the current trends and developments in the study of bacterial and viral fish diseases. Books on these subjects are few and relevant review articles are mostly outdated.It is a valuable aid in maintaining an overview of various facets of the rapidly expanding fields of virology... and useful to the student, teacher, and research scientist.
Keywords: Fish,Fishes; Viruses,Virus diseases